Use of Placentrex to Augment Fertility in Repeat Breeder Cross Bred Cows - KUMAR, K KRISHNA; KUMAR, P SENTHIL; B ANITHA,; P ELANTHALIR,; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 20 healthy, parous, cyclic cross bred cows which were brought to theGynaecological unit of Veterinary College and Research Institute Hospital, Namakkal, Tamil Nadu-637002 with the history of repeat breeding. They were randomly divided in to two groups of 10 animals each.The first group was used as control and the second group was ·treated with IO ml of placentrex,intramuscularly. Both the groups were inseminated twice at 24 hours interval during estrus. The meanduration of estrus was 28. 90 ± 0.41 and 24. 70 ± 0.32 h in control and placentrex administered groups,· respectively, which was significantly shorter (P< 0.05) in placentrex administered group when comparedwith the control group. The proportion of intense, intermediate and weak estrus was 30, 40 and 30 per centin treated group and 20, 40 and 40 per cent in control group, respectively, which was significantlydifferent. The mean length of oestrous cycle in non-conceived cows of treated and control group was 22.25± 0.41 and 22.00 ± 0.64 days, respectively, which was not significantly different. The first serviceconception rate was 60 and 30 per cent in treated and control groups, respectively, which was significantlyhigher (P> 0.05) in the placentrex treated group than the control group.
Keywords: Cross bred cows; Repeat breeder; Placentrex; Conception rate